Antimicrobial Stewardship Programmes: Healthcare Providers' Perspectives on Adopted Hospital Policies That Combat Antibacterial Resistance in Selected Health Facilities in Uganda - Isaac Magulu Kimbowa; Moses Ocan; Mary Nakafeero; Celestino Obua; Cecilia Stålsby Lundborg; Joan Kalyango; Jaran Eriksen (MDPI AG, 2024)
Background: This study aimed to determine healthcare providers' perspectives on adopted hospital policies that support establishing antimicrobial stewardship programmes (ASPs) in selected health facilities in Uganda. Results: In this study, 63.1% of healthcare providers had a low-level perspective regarding adopting hospital policies to facilitate the establishment of ASPs. The low-perspective was significantly associated with females (aOR: 17.3, 95% CI: 1.28-2.34, p < 0.001), healthcare practitioners aged 50 + years (aOR: 1.92, 95% CI: 1.22-3.01, p = 0.004), individuals in the Obstetrics and Gynaecology department (aOR: 1.73, 95% CI: 1.03-2.90, p < 0.037), and Uganda's Eastern (aOR: 1.47, 95% CI: 1.03-2.09, p = 0.034) and Northern regions (aOR: 2.97, 95% CI: 1.63-5.42, p < 0.001). Methods: We conducted a cross-sectional study where 582 healthcare providers (response rate (76%) were interviewed using a questionnaire to assess their perspectives on hospital policies that support ASP in 32 selected health facilities. We performed ordinal logistic regression on factors associated with adopted policies, and these were reported with odds ratios (ORs) and 95% confidence intervals (CIs). Conclusions: there was a low-level perspective on adopted hospital policies to support ASPs, which were significantly associated with the sex of healthcare providers, departments, age, and region of the country.